Students' Mathematical Reflective Thinking Ability Through the Process of Making Telong-Telong Using the Problem-Based Learning Approach - Fina Oktavia; Kashardi Kashardi; Risnanosanti Risnanosanti (Journal of Mathematics Instruction, Social Research and Opinion, 2025)
This research aims to identify and analyze students' mathematical reflective thinking abilities through a Problem-Based Learning (PBL) approach, focusing specifically on making "telong-telong." Mathematical reflective thinking involves students' ability to connect mathematical knowledge with new experiences, find relationships between concepts, and assess and improve their problem-solving strategies. This study follows a qualitative descriptive research design, with a case study approach conducted at SMP Negeri 03 Central Bengkulu, involving 28 students from class IX-A. Data were collected through observations, semi-structured interviews, and documentation, focusing on how students approached mathematical problem-solving tasks in the context of PBL. The findings revealed that students could connect mathematical concepts such as symmetry and geometry to creating "telong-telong," demonstrating their ability to formulate creative solutions and reflect on their problem-solving approaches. Data analysis indicated that PBL facilitated students' critical, creative, and reflective thinking, enabling them to assess and refine their mathematical processes. These results suggest that the PBL approach effectively enhances students' mathematical reflective thinking abilities, providing a more practical and meaningful learning experience.